Antioxidant Activity of Pigmented Rice and Impact on Health - Arifin, Arfina Sukmawati (JURNAL PANGAN, 2019)
The high number of free radicals that are not balanced with the amount of antioxidants in the body triggers oxidative stress. Oxidative stress causes impaired vascular function, damage to proteins and lipids in membrane cell, and nucleic acid (DNA) mutations. Chronic cell damage has a negative effect on tissue that triggers various diseases such as neurodegenerative diseases (Alzheimer's, Parkinson's), cardiovascular diseases (hypertension, arteriosclerosis, and others), cataracts, retinal damage, maculopathy, rheumatoid arthritis, asthma, stroke, diabetes mellitus , immunodepression, cancer, aging, hyperoxia, dermatitis, and others. The application of a healthy lifestyle for example by consuming food sources of bioactive compounds can minimize health risks. Rice is the staple food of the Indonesian people. Some types of rice contain red and black pigments which are known to have high antioxidant activity compared to white rice. The pigment comes from anthocyanin and proanthocyanidin. Various studies in vitro and in vivo prove that anthocyanin and proantocyanidine act as antioxidants and potency as a preventative for various diseases such as cardiovascular, diabetes mellitus, and etc.